1984
DOI: 10.1021/bi00305a014
|View full text |Cite
|
Sign up to set email alerts
|

Physical and enzymatic properties of a class III isozyme of human liver alcohol dehydrogenase: .chi.-ADH

Abstract: chi-Alcohol dehydrogenase (chi-ADH), a class III isozyme characterized by its anodic electrophoretic mobility and lack of inhibition by 4-methylpyrazole, has been isolated from human liver and purified to homogeneity in a reducing medium. chi-ADH resembles other human liver ADH isozymes of classes I and II with respect to its molecular weight, dimeric structure, stoichiometry of zinc and NADH binding, and pH optima for the oxidation of alcohols. This homodimer exhibits subtle differences in its absorption spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 26 publications
6
103
0
Order By: Relevance
“…Inductively coupled plasma emission spectroscopy analyses revealed that AtzB retained 40 to 70% of its metal content after chelator treatment, suggesting that the 1,10-phenanthroline inactivation was not due to metal removal. Wagner, et al observed similar results with human liver alcohol dehydrogenase, concluding that an enzyme-metal-chelator complex was formed which inhibited activity by blocking substrate access to the active site (39).…”
Section: Resultsmentioning
confidence: 70%
“…Inductively coupled plasma emission spectroscopy analyses revealed that AtzB retained 40 to 70% of its metal content after chelator treatment, suggesting that the 1,10-phenanthroline inactivation was not due to metal removal. Wagner, et al observed similar results with human liver alcohol dehydrogenase, concluding that an enzyme-metal-chelator complex was formed which inhibited activity by blocking substrate access to the active site (39).…”
Section: Resultsmentioning
confidence: 70%
“…The moderate inhibition of Mpr activity by EDTA alone and the marginal inhibition by 1,10-phenanthroline suggest that the metal-binding site on the enzyme has a sufficiently high stability constant to render the metal inaccessible to chelating agents. It is noteworthy that others have reported examples of chelating agents being unable to remove the metal ion from some metalloenzymes (4,27).…”
Section: Discussionmentioning
confidence: 99%
“…The horse E subunit is also included since it is the model structure. Both rat and human class I11 enzymes have a greater molar optical absorbance at 280 nm than the class I enzymes, 77.6 x lo3 M -cm-', versus 48.4 x lo3 M-' cm-for the human forms [27].…”
Section: Correlation Of Substitutions With Changes In Physicochemicalmentioning
confidence: 90%
“…2) and Ser in class I1 appears to be of special interest in this respect. Thus, class I enzymes from both rat and human liver [31, 321 have a significant activity at pH 7.5 as compared to pH 10.0, whereas the class I1 [15,33] and class I11 [17,27] enzymes have considerably less activity. Of the enzymes characterized, all with high activity at pH 7.5 have His-51 (liganding to the coenzyme [5,34]), whereas those with low activity do not have His at position 51.…”
Section: Coenzyme-binding Region and The Segment Involved In Subunitmentioning
confidence: 99%